The Ira Moana Project: A Genetic Observatory for Aotearoa’s Marine Biodiversity - Liggins, Libby; Noble, Cory; , The Ira Moana Network (Frontiers in Marine Science, 2021)
The genetic diversity of populations plays a crucial role in ensuring species and ecosystem resilience to threats such as climate change and habitat degradation. Despite this recognized importance of genetic diversity, and its relevance to the Convention on Biological Diversity and the United Nations Sustainable Development Goals, it remains difficult to observe and synthesize genetic data at a national scale. The “Ira Moana – Genes of the Sea – Project” (https://sites.massey.ac.nz/iramoana/) has worked to improve stewardship of genetic data for Aotearoa New Zealand’s (NZ) marine organisms to facilitate marine genetic biodiversity observation, research, and conservation. The Ira Moana Project has established interoperable data infrastructures and tools that help researchers follow international best-practice (including the FAIR Principles for Data Stewardship and CARE Principles for Indigenous Data Governance) and contribute to a national genetic data resource. Where possible, the Project has employed existing infrastructures (such as the Genomic Observatories Metadatabase, GEOME) to allow interoperability with similar research activities, but has also innovated to accommodate the national interests of NZ. The Ira Moana Project has an inclusive model, and through presentations, workshops, and datathons, it has provided training, education, and opportunities for collaboration among NZ researchers. Here, we outline the motivations for the Ira Moana Project, describe the Project activities and outcomes, and plans for future development. As a timely response to national and international pressures on genetic biodiversity research, it is hoped that the Ira Moana Project will facilitate NZ researchers, communities, and conservation practitioners to navigate this crucial period, and provide tangible solutions nationally and globally.